New Microsatellite Markers for Genetic Studies on Sergentomyia schwetzi (Diptera: Psychodidae): A Suspected Vector of Leishmania infantum (Trypanosomatida: Trypanosomatidae) in the Canine Leishmaniasis Focus of Mont-Rolland, Senegal. Issue 6 (18th August 2022) - Prudhomme, Jorian; Mazza, Thomas; Hagen, Sophie; Cassan, Cécile; Toty, Céline; Senghor, Massila Wagué; Niang, Abdoul Aziz; Faye, Babacar; Bañuls, Anne-Laure
Abstract: Visceral leishmaniasis is not endemic in West Africa, but prevalence of canine leishmaniasis and seroprevalence of Leishmania infantum infection in humans are high in the Mont Rolland community (Thiès region, Senegal). Previous studies in this area showed that Sergentomyia schwetzi could be the potential vector of Le. infantum . To precisely describe the biology and population structure of this potential vector, we identified eight novel microsatellite loci to characterize Se. schwetzi populations. We tested these loci in Se. schwetzi populations from five locations at Mont Rolland (Thiès, Senegal). All the loci were polymorphic, with a mean of 17.25 alleles (observed heterozygosity: 0.455). We did not detect any evidence of scoring errors due to stuttering and large allele dropout. Moreover, several of these loci were also amplified in six other sand fly species ( Sergentomyia magna, Sergentomyia dubia, Sergentomyia minuta, Phlebotomus duboscqi, Phlebotomus perniciosus, and Phlebotomus ariasi ). These preliminary results demonstrate the utility of these microsatellite markers for Se. schwetzi (and for the other sand fly species) population genetic studies.